Science-based communication and education needed to improve forest carbon science, policy, and management outcomes - Chad C Papa; Kylie Clay; Lauren T Cooper; Scott C Stark (Environmental Research Letters)
Climate change is one of the most pressing issues facing humanity and forests are increasingly seen as a key pathway to mitigating and adapting to the climate crisis. Because forests stand to play a significant role in reaching net-zero emission targets, politicians and policymakers must act decisively to engineer a rapid paradigm shift that maintains forests’ resilience and adaptive capacity. While there has been significant investment and advancement in forest carbon science to inform policy and planning, there remains a persistent science-practice gap to further integrate scientific information into forest carbon policy and management. Here, we use a survey, semi-structured interviews, and a review of relevant policy literature to assess the nature and extent of, as well as possibilities to bridge, the science-practice gap with regards to forest carbon science, management, and policy. Our results identified barriers to the science-practice gap and provide potential pathways to bridge the divide. We identified three key areas to improve forest carbon outcomes (1) improved data, tools, and models to assess trends and statuses of forests; (2) enhanced carbon science training among state forest practitioners and decision-makers; and (3) effective science-based communication for decision-makers and general audiences. Engagement with forestry stakeholders and iterative and participatory approaches, including targeted education and communication of complex scientific topics, can inform both policy and on-the-ground management. Overcoming such barriers to communication highlights important linkages between forest managers, policymakers, and scientists to address challenges of reaching a net-zero emission.